Implementation of Electronic Systems to Improve Taxpayer Compliance (E-Jurnal Akuntansi, 2024)
This research aims to determine the effect of implementing e-billing and e-filing on taxpayer compliance. Research data was collected using a questionnaire. This research uses individual taxpayers at KPP Pratama West Denpasar as respondents with a total of 100 respondents. The data analysis method used in this research is multiple linear regression analysis using the SPSS program. The research results show that the implementation of e-billing and e-filing can increase taxpayer compliance at KPP Pratama West Denpasar.
Keywords: E-Billing; E-Filing; Taxpayer Compliance